BASIC CHARACTERISTICS AND ROWING TECHNIQUES WITH TOURIST CANOE BOATS - Zvezdan Savić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
By its appearance canoe boats, both competitive and tourist, differ from kayak boats. Main differences are in length, width and the physical appearance of the boats. Canoe rowers use one-leaf paddle, while kayak rowers use two-leaf paddles which are set at the angle of 90 degrees or less. By their main functions, canoe boats can be divided into two groups: 1) competitive and 2) recreational - tourist. Tourist canoe, by its characteristics is a recreational boat for calm waters, though it could be used in the fast - wild waters, in extreme situations. This boat is very stable and a favorite among athletes, campers, adventurers, and all nature lovers. Rowing technique in the tourist boat represents the main way of setting canoe in motion by using the rowers force in specifi c direction. It is, also, the way to keep the canoe stable on the surface. Rowing technique is the same as the rowing mechanics with the competitive canoes. Rower's strokes should be calm, synchronized and long enough, harmonized with the canoe and water movement. They, also, should be mechanically well performed so that the canoe would move in the desired direction. Rowing technique understands fallowing strokes: stroke for moving canoe straight ahead, turning canoe left, right, reverse and for moving sidewise. This paper describes and explains characteristics and mechanics of rowing in the tourist canoe boat